SPEECH ACT OF ULEMA IN COVID-19 PREVENTION APPEAL - Ai Yeni Yuliyanti (Khazanah Multidisiplin, 2022)
Amid deep sadness because of this virus, ulema, as a reference for Muslims, have an important role. This study aims to analyze the speech acts of the ulema in the Friday sermon text at the Great Mosque of Bandung to prove the role of the ulema regarding the appeal for COVID-19 prevention and explore the speech acts of the ulema's directive related to the appeal. This research uses the Speech Act theory with qualitative methods. Data was collected by transcribing the Friday sermon video at the Great Mosque of Bandung during the New Normal period. The results showed that the data contained no assertive, directive, or expressive speech acts. Assertive speech acts dominate, followed by directive speech acts. This dominance is related to the text being a religious text containing religious propositions or teachings. There were also many directive speech acts because the ulema called for the government's appeal regarding the prevention of COVID-19. The dominant directive speech act is requestive. This finding shows that scholars prefer the language of invitation rather than orders. In addition, scholars very often use direct action directive speech acts.